2021
DOI: 10.3389/fpsyt.2021.791991
|View full text |Cite
|
Sign up to set email alerts
|

Cang-Ai Volatile Oil Ameliorates Depressive Behavior Induced by Chronic Stress Through IDO-Mediated Tryptophan Degradation Pathway

Abstract: Background: Cang-ai volatile oil (CAVO) is a Chinese herbal volatile oil. Previous studies report that CAVO exhibits of anti-depressant and anti-inflammatory effects, and modulates activity of monoamine neurotransmitter. The current study sought to explore whether CAVO exhibits anti-depressant effects of CAVO through inhibition of inflammatory response and regulation of indoleamine 2 and 3-dioxygenase (IDO) mediated tryptophan degradation pathway.Methods: The study established chronic unpredictable mild stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Certain essential oils also exhibited appetite-enhancing effects in pathological animal models, including chronic unpredictable mild stress, 5-fluorouracil-induced intestinal mucositis, and high-fat diet (HFD) rat models. The findings showed that long-term inhalation of Cang-ai essential oil significantly improved stress-induced reductions in food intake and body weight in Sprague Dawley rats [74]. Similar results were observed in 5-fluorouracilinduced intestinal mucositis and HFD rat models, in which Amomum villosum Lour.…”
Section: Essential Oils and Fragrant Compounds With Appetite-enhancin...supporting
confidence: 69%
See 1 more Smart Citation
“…Certain essential oils also exhibited appetite-enhancing effects in pathological animal models, including chronic unpredictable mild stress, 5-fluorouracil-induced intestinal mucositis, and high-fat diet (HFD) rat models. The findings showed that long-term inhalation of Cang-ai essential oil significantly improved stress-induced reductions in food intake and body weight in Sprague Dawley rats [74]. Similar results were observed in 5-fluorouracilinduced intestinal mucositis and HFD rat models, in which Amomum villosum Lour.…”
Section: Essential Oils and Fragrant Compounds With Appetite-enhancin...supporting
confidence: 69%
“…For extracting lavender essential oil (Lavandula angustifolia), Satureja khuzistanica, and Hyptis martiusii Benth., n-hexane was not used as a solvent for dissolving the desired essential oils [47,50,64]. Additionally, in the case of Aquilaria crassna, Amomum villosum Lour., Cang-ai, or Arq Zeera essential oils (a distillate prepared from Trachyspermum ammi L., Zingiber officinale Roxb., Carum carvi L., and Cuminum cyminum L.), the dried materials were macerated with distilled water for a period lasting between 1 h and one week before steam distillation [51,58,60,74]. In some cases, essential oils and fragrant compounds were purchased rather than extracted.…”
Section: Essential Oil and Fragrant Compound Preparationmentioning
confidence: 99%
“…CAVO can protect the upper respiratory tract in the smoking mouse model. CAVO can also improve the congestive position of lung tissue and promote cell immune adjustment [23]. However, the effect and mechanism of CAVO in asthmatic animals are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CAVO is extracted from Atractylodes lancea, Ambrosia artemisiifolia, Agastache rugosa, Eupatorium fortunei, Agastache rugosa, etc. CAVO can regulate T-lymphocyte immune response to antirespiratory agents [22,23]. CAVO has been mainly to treat lung inflammation through inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…Cang-ai volatile oil is a Chinese herbal volatile oil that has been used clinically as an intranasal inhaler. Studies have shown that Cang-ai volatile oil can inhibit microglia activation and kynurenine pathway to regulate 5-HT and play an antidepressant effect [ 192 ]. The forced swim test, open field test, sucrose preference test, etc.…”
Section: Intranasal Administration Of Antidepressant Active Ingredientsmentioning
confidence: 99%